Pengaruh Penggunaan POC Air Kelapa terhadap Pertumbuhan dan Hasil Tanaman Kacang Hijau (Vigna Radiata) pada Hidroponik Rakit Apung - Raja Adil Bangun; Devi Andriani Luta; Ariani Syahfitri Harahap (Lembaga Pengembangan Kinerja Dosen, 2025)
This research was conducted on Jalan Tampok, Tanjung Selamat Village, Sunggal District, Deli Serdang Regency, North Sumatra. A non-factorial Randomized Block Design was used, consisting of only one factor, with five treatments and four replications: 0, 1, 2, 3, and 4 liters of coconut water fertilizer. The results showed that the use of coconut water fertilizer had no significant effect on plant height 1, 2, and 3 weeks after planting, and fruit weight per plot. However, it had a highly significant effect on plant height 4 and 5 weeks after planting, stem diameter, number of leaves, and root length. In general, increasing the dosage of coconut water POC tends to result in a better growth response during the vegetative phase of the plant. This suggests that the natural hormones in coconut water can support plant cell division and elongation. However, plant response to treatment is still influenced by environmental factors and dosage, so not all parameters show a significant effect. Further research is needed to determine the optimal dosage that is more effective on production yields.